Pengaruh Permainan Angklung Terhadap Keterampilan Sosial Emosional Anak Usia 5-6 Tahun - Lailiyah, Nazilatul; Reswari, Ardhana (Jurnal Ilmiah POTENSIA, 2026)
Social-emotional skills are the foundation of early childhood development that determine the success of social interactions and emotional regulation in later stages of development. Initial observations at Sejahtera Larangan Luar Pamekasan Kindergarten showed that 67% of children in group B had social-emotional skills that were not yet optimally developed, especially in the areas of cooperation and emotion management. This study aims to determine the effect of angklung games on the social-emotional skills of 5-6-year-old children at Sejahtera Larangan Luar Pamekasan Kindergarten. The research subjects consisted of 15 children. The method used was quantitative research with a one-group pretest-posttest pre-experimental design. The data were analyzed using a paired sample t-test. The results of the study show an increase in the average score from 7.33 to 22.73 with a t-value of -22.680, p<0.001. The absolute value of the t-count (22.680) is greater than the t-table (2.145), so Ho is rejected and H1 is accepted, meaning that angklung games have a significant effect on the social-emotional skills of 5-6 year old children at Sejahtera Larangan Luar Pamekasan Kindergarten. This study recommends integrating angklung games into the early childhood education curriculum as a local culture-based learning strategy to optimize children's social-emotional development.